Jawabanmu

2014-05-08T10:29:31+07:00
X - y + 4 = 0 berarti y = x + 4    atau  x = y - 4

x² + y² + 2x - 5y - 21 = 0  dengan y = x + 4
X² + (x + 4)² + 2x - 5(x+4) - 21 = 0
x² + x² + 8x + 16 + 2x - 5x - 20 - 21 = 0
2x² + 5x - 25 = 0
x1x2 = c/a = -25/2  selanjutnya

x² + y² + 2x - 5y - 21 = 0  dengan x = y - 4
(y - 4)² + y² + 2(y - 4) - 5y - 21 = 0
y² - 8y + 16 + y² + 2y - 8 - 5y - 21 = 0
2y² -11y -13 = 0
y1y2 = c/a= -13/2

x1x2 + y1y2 = -25/2 + (-13/2)
                   = -38/2
                   = -19